Promotion (Study of Legal Protection for E-commerce Consumers) - Hasti Rifah Insani; Kelik Wardiono (Universitas Muhammadiyah Surakarta, 2023)
This research aims to describe the various forms of promotions conducted by businesses and the legal protection available for e-commerce consumers. Promostion is a method employed by companies or businesses to provide direct or e-commerce-based product information to consumers with the aim of making consumers interested the products. E-commerce involves the buying, selling dan marketing of goods or services through electronic media. Based on the discussions conducted, it’s known that forms of promotion include advertisting, personal selling, publicity, public relations and sales promotion. It’s also known that there are still some promotions that don’t have legal protection due to the lack of Indonesian language labelling, provision of false information, pricing discrepancies and fraudulenr elements.